Whipple’s Disease Manifested as Recurrent Ascites - Aamar, Ali (Cureus, 2017)
Whipple’s disease commonly presents as chronic diarrhea and abdominal pain. Ascites is an uncommon presentation of Whipple’s disease. Here, we report a rare case of a 47-year-old male who presented with diarrhea and abdominal distention for three months. The physical examination was significant for ascites. Serum albumin was low and serum-to-ascites albumin gradient was < 1.1 g/dl. This suggested that ascites was less likely to be present due to portal hypertension. Enteroscopy showed erythematous duodenum and jejunum; biopsy was suggestive of periodic acid-Schiff stain (PAS) positive macrophages consistent with Whipple’s disease. During the hospital course, the patient improved with intravenous (IV) ceftriaxone.